QUALITY OF LIFE OF PATIENTS WITH CIRRHOSIS OF THE LIVER - Khusainova Munira Alisherovna; Ergashova Ma’mura Toshtemirovna; Jo’raboyev Madadbek Mukhtorovich; Eliyeva Elnura Oybekovna (Journals Park Publishing, 2022)
More often, cirrhosis develops with prolonged alcohol intoxication (according to various data, from 40-50% to 70-80%) and against the background of viral hepatitis B, C and D (30-40%) and parasitic infections. More rare causes of cirrhosis are diseases of the biliary tract (intra— and extrahepatic), congestive heart failure, various chemical (hepatotoxins) and drug intoxication. Cirrhosis can also develop with hereditary metabolic disorders (hemochromatosis, hepatolenticular degeneration, α1-antitrypsin deficiency) and occlusive processes in the portal vein system (phleboportal cirrhosis).Among the infectious factors: chronic viral hepatitis, especially B and C and parasitic infections, especially fungal and fluke infections (schistosomiasis, opisthorchiasis, candidiasis, aspergillosis). Primary biliary cirrhosis of the liver occurs primarily for no apparent reason. In approximately 10-35% of patients, the etiology remains unclear.  The destruction of hepatocytes is an extremely dangerous process, since these cells perform many important functions: they participate in metabolic processes and secretory activity (excretion of bile and processed substances into the intestine), neutralize toxins and other harmful substances. As a result, the liver ceases to perform its functions in full: harmful substances enter the circulatory system, causing intoxication of the body.
Keywords: cirrhosis; liver; nervous system